SPECIFICS OF PROJECT MANAGEMENT APPLICATION IN AGRIBUSINESS - Marina Viktorovna Korshikova (Science and Innovation Center Publishing House, 2019)
This article discusses the features of project management, the possibility of its application in the organizations of the agro-industrial complex. The analysis of the structure of the agro-industrial complex was made, which allowed to allocate the fourth sphere of organization and management. The features of cost accounting in crop production are revealed and the limitations of the possibility of using the current classification as a source of information in project management are proved. The ways of updating of accounting information are offered. The factors contributing to the spread of project management in agriculture are identified. The allocation of innovative work and undertakings to projects implies the application of project management methods to them, which differ from operational management techniques. Using project management methods allows you to fulfill three main limitations of the project – meet deadlines, do not exceed the budget and perform the amount of work with the declared quality.